2021
DOI: 10.1002/ptr.7312
|View full text |Cite
|
Sign up to set email alerts
|

Biological and pharmacological effects and nutritional impact of phytosterols: A comprehensive review

Abstract: Phytosterols (PSs), classified into plant sterols and stanols, are bioactive compounds found in foods of plant origin. PSs have been proposed to exert a wide number of pharmacological properties, including the potential to reduce total and low‐density lipoprotein (LDL) cholesterol levels and thereby decreasing the risk of cardiovascular diseases. Other health‐promoting effects of PSs include anti‐obesity, anti‐diabetic, anti‐microbial, anti‐inflammatory, and immunomodulatory effects. Also, anticancer effects h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 233 publications
(264 reference statements)
1
49
0
Order By: Relevance
“…In our study, most associations became nonsignificant or inconsistent (i.e., observed in one study period but not in the other) after multivariate adjustment, suggesting that the effect of serum PS on inflammatory markers is small. This finding is in agreement with the conclusion of several systematic reviews and a meta-analysis, showing no significant effect of PS supplementation on inflammatory markers [28,29].…”
Section: Association Between Sterol Levels and Inflammatory Markerssupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, most associations became nonsignificant or inconsistent (i.e., observed in one study period but not in the other) after multivariate adjustment, suggesting that the effect of serum PS on inflammatory markers is small. This finding is in agreement with the conclusion of several systematic reviews and a meta-analysis, showing no significant effect of PS supplementation on inflammatory markers [28,29].…”
Section: Association Between Sterol Levels and Inflammatory Markerssupporting
confidence: 93%
“…PS supplementation attenuated inflammatory pathways in healthy subjects in a proteomics study [27]. On the other hand, a meta-analysis of 20 randomized controlled trials found no significant effect of PS supplementation on inflammatory biomarkers (mainly CRP) in obese patients [28], and a more recent review also reported contradictory findings [29]. Furthermore, most studies relied on supplementation, while population-based studies of PS effects at the usual nutritional intake levels are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…The top four compounds obtained from the compound-target network of USM were stigmasterol, mandenol, sitosterol α 1, and isoarborinol. Stigmasterol and sitosterol α 1 belong to the class of phytosterols as anticancer dietary components [ 25 ]. Stigmasterol inhibited lipopolysaccharide- (LPS-) induced innate immune responses in murine models [ 26 ], significantly reduced the transcription level of TNF- α , destroyed tumor angiogenesis, and reduced the chance of metastasis [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…So, it seems logical that we found more quantity in GF Lv and L Lv (Table 1). Moreover, campesterol and stigmasterol are among the most relevant phytosterols presenting pharmacological and nutritional effects [28]. Consequently, their occurrence in such interesting amounts enhances the L. vulgare's economic value; that is, it stimulates the species use to produce nutraceuticals.…”
Section: Gc-ms Profilementioning
confidence: 99%